Characteristics of Headache After an Intracranial Endovascular Procedure: A Prospective Observational Study. Issue 3 (19th December 2016) - Zhang, Linjing; Wu, Xiancong; Di, Hai; Feng, Tao; Wang, Yunxia; Wang, Jun; Cao, Xiangyu; Li, Baomin; Liu, Ruozhuo; Yu, Shengyuan
Abstract : Background: Two editions of the International Classification of Headache Disorders (ICHD) diagnostic criteria for "Headache attributed to an intracranial endovascular procedure" have been published, in 2004 and 2013. 1, 2 Despite studies that have suggested that the former is not very practical, the ICHD‐3 beta did not contain major changes. Moreover, so far no consensus exists regarding characteristics of headache after intracranial endovascular procedure. Thus, there is a need for sound suggestions to improve the ICHD‐3 beta diagnostic criteria. Methods: Using a prospective design, we identified consecutive patients with unruptured intracranial aneurysms (UIAs) with neuroendovascular treatment from January 2014 to December 2014. Results: In total, 73 patients were enrolled, and 58 patients ultimately completed the 6‐month follow‐up. After the procedure, five of the 29 patients (17.2%) with pre‐existing headache experienced marked worsening after the procedure, while seven of the 29 patients without prior headache developed new‐onset headache post‐procedurally. The headaches started within 24 hours, with a mean duration of 24‐72 hours. The headaches were moderate to severe. The eligibility of these events to be considered headaches caused by neuroendovascular procedures according to the ICHD‐3 beta diagnostic criteria for designation was far from ideal. Conclusions: Most cases of markedly worsening headaches and new‐onset headaches started within 24 hours and persisted longer than that specified in the ICHD‐3 beta diagnostic criteria. Moreover, considering that some items are not very practical, the ICHD‐3 beta diagnostic criteria should be revised in the light of recent literature reports.